URGENSI DISIPLIN KERJA GURU SMA SWASTA NURUL ARAFAH BAKTIYA KABUPATEN ACEH UTARA - Ibnu Hajar (Universitas Negeri Medan, 2022)
Nurul Arafah Baktiya Private High School Teacher Private High School Teacher Urgent Work Discipline. This research aims to explain about the urgency discipline of private high school teachers Nurul Arafah Baktiya District of North Aceh in obeying school rules, respect the norms and rules that apply. The method used in this research is qualitative with primary data source result of field interview, observation and documentation. Interviews were conducted with informants who were determined by purposive sampling ie informants with criteria that were appropriate to the research: Principal, Teacher, Student and Committee. The result of his research is private high school teachers Nurul Arafah Baktiya North Aceh district has not fully respect the rules and norms that apply in schools. Private High School Teachers Nurul Arafah does not respect religious norms, morality norms, norms of decency and legal norms. This attitude is also driven by several things, namely the absence of exemplary school principals, the absence of strict supervision from the principal, does not provide adequate welfare for teachers, does not impose sanctions for those who violate the rules,